2023
DOI: 10.34067/kid.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

Needle Angle Matters: An Investigation of the Effect of Needle Angle on Hemodialysis Cannulation Skill

Abstract: Background: Cannulation is critical for maintaining a functional vascular access for patients on hemodialysis. However, relatively little is known about the quantitative aspects of needle insertion dynamics required for skilled cannulation. In this paper, we introduce three kinds of metrics that quantify needle insertion angle — recognized as important for safe and effective cannulation — during cannulation on an instrumented simulator for skill assessment. Three questions were examined in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Subgroup analysis within the intervention group revealed no significant differences in pre- or post-dialysis levels or Kt/V based on time to intervention. Zhang et al 36 showed that compared with the metal steel needle group, the dialysis indwelling needle group had higher haemodialysis adequacy. This may be because the dialysis indwelling needle is designed with a flat head and a side hole, and the indwelling needle material is polytetrafluoroethylene, which can stretch under the influence of body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis within the intervention group revealed no significant differences in pre- or post-dialysis levels or Kt/V based on time to intervention. Zhang et al 36 showed that compared with the metal steel needle group, the dialysis indwelling needle group had higher haemodialysis adequacy. This may be because the dialysis indwelling needle is designed with a flat head and a side hole, and the indwelling needle material is polytetrafluoroethylene, which can stretch under the influence of body temperature.…”
Section: Discussionmentioning
confidence: 99%